Voix rebelle(s) : minoration / re-création / révolution dans quatre romans de Toni Morrison - Marlène Barroso-Fontanel (Babel: Littératures Plurielles, 2019)
Morrison (Toni) Revolution implies movement which is at the heart of Toni Morrison’s work. According to her, writing belongs to the realms of creation and politics. Language is a means of both resistance and liberation that she uses to fight against the hegemony of the major voice. Her novels are a way for her to bring the margin of the American society to light and to offer another view of History through her characters. Minoration is then to be understood as (re-)creation in Toni Morrison’s work where she enables the reader to listen to « [l]es éclats de la parole » [Glissant 121] of those who fight against their disappearance. Toni Morrison’s writing therefore rings out with rebellious voices through which the author undermines the major language so as to give rise to « un devenir-autre de la langue » [Deleuze 15].